Turbulent channel flow simulations using the lattice Boltzmann method with near-wall modeling on a non-body-fitted Cartesian grid. (1st July 2021) - Maeyama, Hirotaka; Imamura, Taro; Osaka, Jun; Kurimoto, Naoki
Abstract: A novel near-wall modeling for large-eddy simulation based on the lattice Boltzmann method is proposed. An existing near-wall modeling based on the reconstruction of distribution functions is further developed to calculate high Reynolds number wall-bounded turbulent flow on a non-body-fitted Cartesian grid. The following three ideas are introduced into the existing reconstruction model: (1) the introduction of an image-point, (2) blending of sub-grid scale and Reynolds-averaged Navier-Stokes eddy viscosity considering the Reynolds shear stress resolved on a computational grid, and (3) modifications of velocity and eddy viscosity profiles near a wall. For the validation of the proposed model, numerical simulations of a turbulent channel flow on a non-body-fitted Cartesian grid are performed. Three different cases of the angles between the Cartesian grid line and the wall boundary are calculated, and the calculation results are compared with the results of direct numerical simulation or a semi-analytical profile in terms of streamwise velocity, resolved Reynolds shear, and normal stress profiles. The proposed model is robust and accurate, yielding highly satisfactory results regardless of the angles between the Cartesian grid line and the wall boundary.